IMPROVEMENT OF MECHANISMS FOR FORMING A DIGITAL SYSTEM OF HOUSING AND COMMUNAL SERVICES (ON THE EXAMPLE OF THE CITY OF KARSHI) - F.D. Jo'rayev; Khujakulova Maftuna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This scientific article provides a comprehensive analysis of the digitalization process in the field of housing and communal services using the example of Qarshi city. The study examines the theoretical foundations, practical implementation, and existing challenges of digital management systems and proposes effective mechanisms to address them. The suggested approaches aim to improve service quality, streamline management processes, and enhance transparency in the services provided to the population.